Developing intercultural perspectives on language use exploring pragmatics and culture in foreign language learning - McConachy, Troy 1980- (Languages for intercultural communication and education, 2018)
"Many teachers recognise the importance of integrating intercultural learning into language learning. This book argues that teachers can work creatively with conventional resources and utilise classroom experiences in order to help learners develop awareness of the influence of cultural assumptions and values on language use"--Provided by publisher.